2018
DOI: 10.1371/journal.pone.0201230
|View full text |Cite
|
Sign up to set email alerts
|

Projected effectiveness of mandatory industrial fortification of wheat flour, milk, and edible oil with multiple micronutrients among Mongolian adults

Abstract: Industrial fortification of wheat flour is a potentially effective strategy for addressing micronutrient deficiencies in Mongolia, given its ubiquitous consumption and centralized production. However, Mongolia has not mandated fortification of any foods except for salt with iodine. This study modeled the effectiveness and safety of mandatory industrial fortification of wheat flour alone and in combination with edible oil and milk in reducing the prevalence of multiple micronutrient intake deficiencies among he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…Fourth, despite the size and breadth of the study population (comprising 1838 person-days of summer and winter prospective dietary intake from urban and rural men and women in 8 national provinces), and the use of random sampling within each province, the study population is not intended to be nationally-representative and results should be interpreted in the context of the sampling frame. Readers of our earlier fortification modeling study [16], which includes national estimates for the baseline prevalence of dietary inadequacy of ten nutrients using data from the same population as the present study, will note moderate quantitative differences between those and the present results for thiamin and vitamin A in some subgroups. These differences may be attributable to differing methodologies used in estimating intake distributions as well as our earlier use of survey weights.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Fourth, despite the size and breadth of the study population (comprising 1838 person-days of summer and winter prospective dietary intake from urban and rural men and women in 8 national provinces), and the use of random sampling within each province, the study population is not intended to be nationally-representative and results should be interpreted in the context of the sampling frame. Readers of our earlier fortification modeling study [16], which includes national estimates for the baseline prevalence of dietary inadequacy of ten nutrients using data from the same population as the present study, will note moderate quantitative differences between those and the present results for thiamin and vitamin A in some subgroups. These differences may be attributable to differing methodologies used in estimating intake distributions as well as our earlier use of survey weights.…”
Section: Discussioncontrasting
confidence: 50%
“…Inadequate intake of calcium, vitamin D, and magnesium may jointly contribute to the relatively high prevalence of osteoporosis in Mongolian adults [35], and low intake of fiber has been linked to higher risk of heart disease, type 2 diabetes, and metabolic syndrome in large prospective cohort studies [36][37][38]. Implications of observed deficits of folate and other nutrients are discussed in previous studies by our group [16], in which we have also suggested evidence-based interventions to reduce the prevalence of micronutrient deficiency in the Mongolian population, including industrial food fortification and micronutrient supplementation [9,16,39]. As micronutrients work together to allow healthy body functioning and prevent disease, addressing multiple inadequacies (particularly through large-scale diet modification in the long term) may reap multiplicative benefits, and ensuring adequate micronutrient intake should remain integral to Mongolia's national health policy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical analyses of Chinese children have found a high prevalence of calcium, iron, zinc, and selenium deficiency; high prevalence of mild iodine deficiency, marginal vitamin A deficiency, and vitamin D insufficiency; and moderate prevalence of thiamine, riboflavin, and vitamin B12 deficiency nationwide [4]. In a Mongolian nationwide survey from 2012 to 2016, dietary inadequacies of thiamin, folate, and vitamins A, D, and E were common among Mongolian adults [5], while a 2006 study of young children aged 6–24 months noted dietary inadequacies of calcium, iron, zinc, and vitamins A and C to be of concern [6]. Biochemical deficiencies of iron, zinc, folic acid, and vitamins A and D have been reported among Mongolian women of reproductive age and young children [2,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Mongolia’s small population and centralized production of staple foods should facilitate expanded fortification legislation there [5]. Eleven years after the conclusion of an Asian Development Bank-funded infrastructural project and effectiveness trial [7,19], renewed public sector advocacy efforts led the Mongolian parliament to pass a law in April 2018 expanding mandatory industrial fortification beyond that of salt; national program implementation is planned in January 2020 [20].…”
Section: Introductionmentioning
confidence: 99%